Protecting public health and the environment: towards a general ban on cellulose acetate cigarette filters in the European Union - Everaert, Stijn; Schoeters, Greet; Lardon, Filip; Janssens, Annelies; Van Larebeke, Nicolas; Raquez, Jean-Marie; Bervoets, Lieven; Spanoghe, Pieter (Frontiers in Public Health, 2023)
After the establishment of a causal relationship between tobacco use and cancer in the 1950s, cellulose acetate filters were introduced with the claim to reduce the adverse health impact of unfiltered cigarettes. Often perceived to be more pleasant and healthy, filters encouraged smoking. However, filtered cigarettes are more deeply inhaled to obtain the same nicotine demand while altered combustion releases more tobacco-specific nitrosamines. The increasing use of cigarette filter ventilation is associated with a sharp rise in lung adenocarcinomas in recent decades. While not preventing adverse health effects, a global environmental problem has been created due to the non-biodegradable filter litter, causing ecotoxicological effects and the spread of microplastics. Recently, the Belgian Superior Health Council advised policymakers to ban cigarette filters as single-use plastics at both national and European levels. This article outlines the arguments used to justify this plea (human health and environment), the expected effects of a filter ban, as well as the public reception and reactions of the tobacco industry. The specific context of the European Union is discussed including the revision of the Single-Use Plastics Directive, affording a new opportunity to ban plastic filters. This perspective article aims to fuel the momentum and cooperation among member states for this purpose.